Non‐Correlated Variation of Leaf and Fine Root Traits in Subtropical Forest Plants - Yuzhi Zhu; Meng Li; Junyong Zheng; Yongqiang Wang; Yanghang Ren; Han Zhang; Zeyu Feng; Sandy P. Harrison; I. Colin Prentice; Yue Zhang; Lewei Jin; Shuang Sun; et al. (Ecology Letters, 2026)
Plants employ multiple strategies to adapt to their growth environment. Characterizing key dimensions in plant trait space is important for understanding functional diversity within ecosystems. Leaf and root functional traits have been studied in the context of resource economics, but whether they covary, and through which mechanisms, is still debated. We investigated this in subtropical forests by sampling root and leaf traits on individuals of co‐existing species in two communities with different resource availability. We found largely non‐correlated variation between leaf and fine root traits both across and within communities, and a clear decoupling between leaf economic spectrum and root economic space, independent of evolutionary history. Our results suggest that leaf‐root trait relationships are shaped by an interplay between microenvironmental heterogeneity that drives decoupling and shared selection pressures promoting covariation. The interplay explains the weak observed coordination and highlights the importance of environmental context in predicting above‐ and below‐ground plant functions.